EXPLORING THE ESSENCE OF INDONESIAN SECURITIES-BASED CROWDFUNDING - Koeswidi Astuti, Nanin; Suhariningsih,; Sukarmi,; Hamidah, Siti (International Journal of Law in Changing World, 2024)
In Indonesia, crowdfunding is widely acknowledged as a collaborative financing method, enabling businesses, projects, or initiatives to raise funds through community engagement on online platforms. This collective funding strategy serves a variety of purposes, including support for humanitarian causes, education, business ventures, political campaigns, public infrastructure, and innovative endeavors. Crowdfunding has risen to prominence as a vital financial tool for entrepreneurs in search of capital, leading to significant expansion in this funding model. The regulatory framework in Indonesia has undergone evolution, transitioning from Equity Crowdfunding to Securities Crowdfunding (SCF). SCF stands out as a remarkable alternative to conventional non-bank funding, offering manifold advantages for business development by encouraging creativity and innovation. Despite its beneficial impact, regulatory challenges remain, particularly in implementing rules consistently across diverse business entities involved in crowdfunding, regardless of their profit or non-profit objectives. This study seeks to illuminate critical areas that warrant careful consideration by the Indonesian government in the domain of crowdfunding regulation. While current regulations are predominantly centered on securities crowdfunding, there are still uncertainties concerning the foundational principles and aims of crowdfunding. This situation poses a pivotal question: What trajectory does the Indonesian government envision for crowdfunding activities — a focus on profit generation or a dedication to non-profit pursuits? This highlights the pressing necessity for a thorough review and detailed examination of the existing regulations, aiming to establish guidelines that protect the interests of all stakeholders, thereby averting any perception of unfairness or exploitation. __________ En Indonesia, el crowdfunding es ampliamente reconocido como un método de financiación colaborativo que permite a empresas, proyectos o iniciativas recaudar fondos a través de la participación comunitaria en plataformas en línea. Esta estrategia de financiación colectiva tiene varios propósitos, incluido el apoyo a causas humanitarias, educación, proyectos comerciales, campañas políticas, infraestructura pública y esfuerzos innovadores. El crowdfunding ha cobrado importancia como una herramienta financiera vital para los emprendedores que buscan capital, lo que ha llevado a una expansión significativa de este modelo de financiación. Además del crecimiento continuo de las actividades de financiación colectiva, el gobierno de Indonesia ha estado mejorando activamente las regulaciones relacionadas con la financiación colectiva. Este esfuerzo es evidente en la evolución regulatoria del Equity Crowdfunding (ECF) al Securities Crowdfunding (SCF). SCF se destaca como una alternativa excepcional a la financiación no bancaria tradicional. Ofrece importantes ventajas para el crecimiento empresarial al fomentar la creatividad y la innovación. Estos cambios regulatorios en Indonesia demuestran la dedicación del gobierno para hacer del crowdfunding una opción financiera más efectiva y accesible. El crowdfunding ofrece importantes beneficios; sin embargo, enfrenta desafíos regulatorios, particularmente en la implementación consistente de reglas en varias entidades comerciales involucradas en el crowdfunding, independientemente de sus motivos lucrativos o no lucrativos. El presente estudio se esfuerza por identificar y discutir áreas críticas que requieren una cuidadosa consideración por parte del gobierno de Indonesia al regular las actividades de financiación colectiva. Aunque las regulaciones existentes se centran principalmente en el crowdfunding de valores, persisten ambigüedades con respecto a los principios y objetivos fundamentales del crowdfunding en su conjunto. Esta ambigüedad suscita una pregunta crucial: ¿Considera el gobierno de Indonesia el crowdfunding principalmente como una herramienta para generar ganancias o como un medio para apoyar iniciativas sin fines de lucro? Es evidente la necesidad de un examen exhaustivo y detallado de las regulaciones existentes, con el objetivo de establecer directrices que salvaguarden los intereses de todas las partes interesadas y excluyan cualquier percepción de injusticia o explotación. __________ 在印度尼西亚，众筹被广泛认为是一种协作融资方式，使企业、项目或倡议能够通过在线平台上的社区参与筹集资金。这种集体融资策略服务于各种目的，包括对人道主义事业、教育、商业企业、政治活动、公共基础设施和创新努力的支持。众筹作为一种重要的金融工具，为寻找资金的企业家提供了重要的支持，使得这种融资模式得到了显著的扩展。除了众筹活动的持续增长外，印尼政府还一直在积极完善与众筹相关的法规。从股权众筹（ECF）向证券众筹（SCF）的监管演变就证明了这一点。证券众筹作为一种非传统的非银行融资方式脱颖而出。它通过鼓励创造力和创新，为企业成长提供了显著的优势。印尼的这些监管变化表明，政府致力于使众筹成为一种更有效、更便捷的金融选择。 众筹虽然带来了显著的好处，但它也面临着监管方面的挑战，特别是在各种从事众筹的商业实体中一致实施规则方面，无论其是出于盈利还是非盈利动机。本研究旨在确定并讨论印尼政府在规范众筹活动时需要考虑的关键领域。虽然现行法规主要关注证券众筹，但关于众筹作为一个整体的基本原则和目标仍存在歧义。这种歧义引出了一个关键问题：印尼政府是将众筹主要视为一种盈利工具，还是支持非盈利倡议的手段？显然，我们需要对现有法规进行全面而详细的审查，目的是制定保障所有利益相关者利益的指导方针，并排除任何不公平或剥削的观点。